Dietary B-complex vitamins and sleep quality in relation to cognitive impairment among older adults: non-linear associations and evidence of additive interaction - Zhang, Meihui; Wang, Yuxuan; Zhang, Yinghuan; Gao, Quyige; Hu, Fan; Wang, Ying; Shao, Chunhai; Cai, Yong (Frontiers in Nutrition, 2025)
BackgroundGlobal dementia cases are projected to reach 152.8 million by 2050, with China accounting for approximately 25% of cases. While B-complex vitamins and sleep quality are established modifiable determinants of cognitive health, their potential synergistic effects on cognitive function remain unexplored, particularly in rapidly aging populations.MethodsIn this population-based cross-sectional study, we analyzed baseline data from 8,806 adults aged ≥65 years in the Shanghai Aging and Retirement Evaluation Survey (January-May 2024). Dietary B-complex vitamins intake was assessed using a validated Food Frequency Questionnaire. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Cognitive function was measured using the Mini-Mental State Examination, with scores ≤ 24 indicating cognitive impairment. We examined non-linear relationships using restricted cubic splines analysis and assessed independent associations using multivariate logistic regression. Both multiplicative and additive interactions were evaluated using cross-product terms and three additive interaction indices.FindingsAmong 8,806 participants, 677 (7.69%) had cognitive impairment. Higher intake of vitamin B6, B12, and folate showed L-shaped associations with reduced cognitive impairment risk, while PSQI scores demonstrated J-shaped relationships. Compared with lowest quartiles, participants in highest quartiles of vitamin B6, B12, and folate intake had lower odds of cognitive impairment (adjusted OR 0.33 [95% CI: 0.25–0.43], 0.43 [95% CI: 0.33–0.55], and 0.33 [95% CI: 0.25–0.43], respectively; all p < 0.001), while those with highest PSQI scores had increased odds (2.94 [95% CI: 2.34–3.69], p < 0.001). Significant additive interactions between low B-complex vitamins intake and poor sleep quality were observed (Relative Excess Risk Due to Interaction 0.97 [95% CI: 0.48–1.46]; Attributable Proportion 0.22 [95% CI: 0.10–0.35]; Synergy Index 1.41 [95% CI: 1.14–1.67], all p < 0.001), suggesting a synergistic association with cognitive impairment risk.InterpretationOur findings reveal a synergistic association of adequate B-complex vitamins intake and good sleep quality with a lower prevalence of cognitive impairment in older adults, suggesting that integrated interventions targeting both nutritional and sleep factors might be more effective than single-domain approaches in preserving cognitive health during aging.